Effectiveness of using geogebra software on students’ understanding of the concept of circles - Shadaan, P.; Leong, K.E. (2013)
The use of technology in the pedagogical process is growing at phenomenal rate, due to the vast availability of gadgets. Further, it is a challenging task for teachers to engage their students without technology integration, due to its popularity amongst their students. As a result, educationists see the urgent need of technology integration in students’ mathematical activities. Therefore, the purpose of this experimental study was to identify whether GeoGebra enhances students’ understanding of the concept of circles. Fifty-three grade nine students participated in this study and students were provided with six activities using GeoGebra to study the concept of circles. As a part of the quantitative analysis, survey questionnaires were distributed to the students and the results interpreted statistically. The results of this study showed that there existed a significance difference between the experimental and control group of students in understanding and analysing the concept of circles.